INTERPLAY BETWEEN DISORDER AND ELECTRON INTERACTIONS - MEAN-FIELD PHASE-DIAGRAM OF AN ANDERSON-HUBBARD MODEL - Logan, D; Tusch, M (1993)
To obtain a broad understanding of the combined effects of disorder and electron interactions, the phase diagram of a half-filled Gaussian site-disordered Anderson-Hubbard model is assessed numerically on a simple cubic lattice, at the unrestricted Hartree-Fock mean field level. Metallic/insulating and magnetic phases are considered. Paramagnetic, disordered antiferromagnetic and spin glass magnetic phases are found. Particular attention is given to obtaining a microscopic picture of the interplay between disorder and interaction-induced local moment formation, which underlies the metal-(gapless) insulator transition. © 1993.